Stretch-resistant packing belt and preparation method thereof
Through the process of modifying montmorillonite/Fe3+sulfonated polyphenylene ether/polyacrylamide crosslinking materials, the problems of low tensile performance of the packaging belt and the quality of heat treatment products are solved, and the high tensile strength and flame retardant performance are improved. Suitable for a variety of packaging needs.
Patent Information
- Application Number
- CN202411428334.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
The tensile performance of existing packaging belts is low and prone to fracture when impacted by a large external force. The particle size of the heat treatment products is uneven and impurities exist, which affects the mechanical strength.
The modified montmorillonite/Fe3+sulfonated polyphenylene ether/polyacrylamide crosslinking material is used to prepare tensile-resistant packaging belts through stirring, extrusion, cooling and curing processes to form a material structure with high thermal stability and elastic behavior.
It significantly improves the tensile strength and flame retardant properties of the packaging belt, enhances the toughness and thermal stability of the material, and adapts to different usage needs.
Smart Images

Figure BDA0005082835150000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging product preparation, and in particular relates to an anti-stretching packaging belt and a preparation method thereof. Background Art
[0002] Strapping tape is a common packaging material. Packaging strapping tape (strapping tape) is made of polyethylene, polypropylene resin, cold-rolled steel strip as the main raw materials, and also made of nylon and polyester as raw materials. It is made by extrusion, uniaxial stretching, and heat treatment and bluing. In addition to being used for sealing and strapping corrugated boxes, hot-rolled steel coils, and cold-rolled steel coils, strapping tape can also be used to strap glass, pipes, materials, fruits, etc.
[0003] The tensile properties of strapping tape have a great influence on its use. When strapping tape with low tensile strength is subjected to a large external impact, it may break due to its low strength. The tensile strength of strapping tape made of ordinary polymer materials is about 200MPa, which cannot adapt to impacts under higher strength, otherwise it will break.
[0004] The patent application with publication number CN 110028775 A discloses a method for preparing a tensile-resistant strapping tape material, which generates free radicals such as hydroxyl and carboxyl groups on the surface of polymer fibers, so that the fiber components can bond the various components in the material after being introduced into the strapping tape material, thereby improving the mechanical strength of the strapping tape material; although the tensile resistance of the strapping tape is improved, the raw materials of the heat-treated product are cotton and crop straw, etc., and there may be problems such as large particle size differences and impurities during the processing process, and the dispersion is poor, thereby affecting the overall mechanical strength of the strapping tape. Therefore, designing a strapping tape with high tensile strength and high mechanical properties to meet the needs of different situations is an urgent problem to be solved at this stage. Summary of the invention
[0005] The object of the present invention is to provide a tensile-resistant strapping tape and a preparation method thereof, so as to solve the problem that the strapping tape has low strength and is easy to break under strong tension.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A tensile-resistant strapping tape, comprising, by weight, modified montmorillonite / Fe 3+ The sulfonated polyphenylene ether / polyacrylamide cross-linking material is 15-20 parts, polyurethane is 19-21 parts, polystyrene is 9-12 parts, dihexyl glutarate is 4-6 parts, and polyimide is 18-21 parts, and the mixture is obtained through stirring, extruding, cooling and solidification.
[0008] Furthermore, the modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material is prepared by the following steps:
[0009] The first step is to dissolve sulfonated polyphenylene ether and polyacrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile in 1-methyl-2-pyrrolidone to obtain a reaction solution;
[0010] In the second step, montmorillonite is added to the FeCl3 solution, ultrasonically dispersed to obtain a dispersion, and then the dispersion is added to the reaction solution, heated and stirred, and polymerized to obtain a modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material.
[0011] Furthermore, the mass ratio of sulfonated polyphenylene ether, polyacrylamide, ethylene glycol dimethacrylate, azobisisobutyronitrile and 1-methyl-2-pyrrolidone in the reaction solution is 5-20:5-20:1-2:1-2:200-220.
[0012] Furthermore, the mass ratio of montmorillonite to FeCl3 solution in the dispersion is 10-20:150-160.
[0013] Furthermore, the mass ratio of the reaction liquid to the dispersion liquid is 220-250:160-180.
[0014] Further, the reaction solution was stirred at 40°C for 10 min, the dispersion was ultrasonically dispersed (45 kHz, 20 min), the dispersion and the reaction solution were mixed and stirred at 55-60°C for 2 h, and the mixed sample was polymerized in an oven at 80°C for 23-24 h.
[0015] Furthermore, sulfonated polyphenylene ether is prepared by the following method: polyphenylene ether is prepared in chloroform with chlorosulfonic acid as a sulfonating agent, stirred at room temperature, and chlorosulfonic acid and polyphenylene ether are gradually added to the chloroform solution. After reacting for 30 to 35 minutes, the solution is precipitated, filtered, washed with distilled water, and dried in vacuo.
[0016] Furthermore, the mass ratio of the chlorosulfonic acid to the polyphenylene ether is 10-12:5-6.
[0017] A method for preparing a stretch-resistant strapping tape comprises the following steps:
[0018] Modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material, polyurethane, polystyrene, dihexyl glutarate, and polyimide are put into a reaction kettle and stirred to obtain a prefabricated hot melt slurry, which is immediately put into a twin-screw extruder, extruded into a mold, cooled and solidified, and then demolded to obtain a tensile-resistant strapping tape material.
[0019] Further, the temperature in the reactor was raised to 195-210° C., and the mixture was stirred at a speed of 300 r / min for 2 h to obtain a prefabricated hot melt slurry.
[0020] Furthermore, the extrusion temperature of the twin-screw extruder is 195-210°C.
[0021] Beneficial effects of the present invention:
[0022] (1) Fe used in the present invention 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked network structure, Fe 3+ The metal ion coordination of sulfonated polyphenylene ether is used for the first brittle network structure, and the soft chemically cross-linked polyacrylamide is used for the second ductile network structure. The first network is easily broken when deformed, thereby dissipating a large amount of energy; while the elastic behavior of the second network maintains the shape and gives the material a certain elasticity, exhibiting a higher heat resistance temperature and elastic behavior, with high thermal stability and improved tensile resistance.
[0023] (2) The modified montmorillonite used in the present invention has a larger lattice spacing after modification, and its specific surface area and adsorption capacity are significantly increased. It has good dispersion performance, enhances the comprehensive physical properties of the polymer, increases the decomposition temperature and residual carbon rate of the material, and thus improves the flame retardant properties of the material.
[0024] (3)Fe 3+ Fe in sulfonated polyphenylene ether 3+ As a Lewis acid, Fe 3+ Forming ~SO3 with sulfonated polyphenylene ether - -Fe 3+ -SO3 - ~ ion coordination bond, forming Fe 3+ The sulfonated polyphenylene ether chain is rigid and brittle. The ion complex formed after ion coordination consumes energy during the deformation process, thereby giving the material toughness, increasing the material's fracture stress, and improving the tensile strength. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] This embodiment provides a stretch-resistant strapping tape, which is prepared by the following steps:
[0028] 1) Preparation of sulfonated polyphenylene ether
[0029] Polyphenylene ether is prepared in chloroform with chlorosulfonic acid as the sulfonating agent. 10 mL of chlorosulfonic acid (10 wt%) is gradually added to 20 mL of polyphenylene ether (5 wt%) chloroform solution under mechanical stirring at 25° C. After reacting for 30 minutes, the product is precipitated, filtered, washed with distilled water, and dried in vacuo.
[0030] 2) Preparation of modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material
[0031] In the first step, 2 g of sulfonated polyphenylene ether and 2 g of polyacrylamide, as well as 0.2 g of ethylene glycol dimethacrylate and 0.2 g of azobisisobutyronitrile were dissolved in 20 mL of 1-methyl-2-pyrrolidone and stirred at 40° C. for 10 min to obtain a reaction solution;
[0032] In the second step, 2 g of montmorillonite was added to 15 mL of FeCl3 solution (1 mol / L), and ultrasonic dispersion was performed at 45 kHz for 20 min to obtain a dispersion. The dispersion was then added to the reaction solution, heated and stirred at 60 °C for 2 h, and polymerized in an oven at 80 °C for 24 h to obtain a modified montmorillonite / FeCl3 solution. 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material.
[0033] 3) Preparation of anti-stretch strapping materials
[0034] By weight, 15 parts of modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material, 20 parts of polyurethane, 10 parts of polystyrene, 5 parts of dihexyl glutarate, and 20 parts of polyimide are put into a reactor, the temperature in the reactor is raised to 200°C, and a stirring device is used to stir at a speed of 300r / min for 2 hours to obtain a prefabricated hot melt slurry, which is immediately put into a twin-screw extruder, extruded into a mold at an extrusion temperature of 200°C, and demolded after cooling and curing to obtain the tensile-resistant strapping tape material.
[0035] Example 2
[0036] The present embodiment is different from the embodiment 1 in that “2 g of sulfonated polyphenylene ether and 2 g of polyacrylamide” is changed to “0.5 g of sulfonated polyphenylene ether and 2 g of polyacrylamide”.
[0037] The remaining raw materials and preparation process remain the same as in Example 1.
[0038] Example 3
[0039] The present embodiment is different from the embodiment 1 in that “2 g sulfonated polyphenylene ether and 2 g polyacrylamide” is changed to “2 g sulfonated polyphenylene ether and 0.5 g polyacrylamide”.
[0040] The remaining raw materials and preparation process remain the same as in Example 1.
[0041] Example 4
[0042] The difference between this embodiment and embodiment 1 is that "2g montmorillonite" is changed to "1g montmorillonite";
[0043] The remaining raw materials and preparation process remain the same as in Example 1.
[0044] Example 5
[0045] The difference between this embodiment and embodiment 1 is that "15 parts of modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material" was changed to "5 parts modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material".
[0046] The remaining raw materials and preparation process remain the same as in Example 1.
[0047] Example 6
[0048] The difference between this embodiment and embodiment 1 is that "15 parts of modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material" was changed to "25 parts modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material".
[0049] The remaining raw materials and preparation process remain the same as in Example 1.
[0050] Example 7
[0051] The present embodiment is different from the embodiment 1 in that the temperature in the reaction kettle is set to 210° C. and the extrusion temperature of the twin-screw extruder is set to 210° C.
[0052] The remaining raw materials and preparation process remain the same as in Example 1.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that "polyacrylamide" is replaced by "polyethyl acrylate".
[0055] The remaining raw materials and preparation process remain the same as in Example 1.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 is that no FeCl3 is added.
[0058] The remaining raw materials and preparation process remain the same as in Example 1.
[0059] Comparative Example 3
[0060] The difference between this comparative example and Example 1 is that no montmorillonite is added.
[0061] The remaining raw materials and preparation process remain the same as in Example 1.
[0062] Performance tests were conducted on Examples 1 to 7 and Comparative Examples 1 to 3. The tensile strength was tested using a tensile strength testing machine. The impact strength test was conducted according to standard GB / T 1043.1-2008. The flame retardant properties were tested according to standards GB / T 2408-2021 and GB / T 2406.2-2009. The results are shown in Table 1:
[0063] Table 1
[0064]
[0065] It can be seen from Table 1 that the tensile strength of Example 1 reaches 315MPa and the impact strength is 4.2kJ / m 2 , LOI value reached 28.2%, UL94 grade was V-0. Compared with Example 1, Example 2-3 showed a weakening of mechanical strength, which may be due to the change of material ratio leading to unstable cross-linking structure; compared with Example 1, Example 4 mainly showed a decrease in UL94 grade, indicating that the modified montmorillonite played a flame retardant role; Examples 5-6 determined the modified montmorillonite / Fe 3+ The optimal ratio of sulfonated polyphenylene ether / polyacrylamide cross-linked material; Example 7 determines the optimal temperature for preparing strapping tape.
[0066] Compared with Example 1, the flame retardant performance of Comparative Example 1 is reduced, because the introduced polyacrylamide improves the flame retardancy of the material relative to polyethyl acrylate; compared with Example 1, the overall performance of Comparative Example 2 is reduced, because FeCl3 is not only a modifier of montmorillonite, but also increases the distance between the montmorillonite lattices, making it more adsorbable, and Fe 3+ Ionic coordination bonds are formed between sulfonated polyphenylene ethers to form a complex, which enhances the toughness of the material; Compared with Comparative Example 1, the UL94 grade of Comparative Example 3 is V-2, because the modified montmorillonite acts as a physical and chemical cross-linking barrier, extending the migration path of heat, volatile combustible gases and solid particles, so the modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material has better flame retardant effect.
[0067] In summary, the tensile-resistant strapping tape prepared by the present invention has high tensile strength, high impact strength, good flame retardant effect, and has broad application prospects.
[0068] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A tensile-resistant strapping tape, characterized in that: By weight, it includes the following raw materials: modified montmorillonite / Fe 3+ 15-20 parts of sulfonated polyphenylene ether / polyacrylamide cross-linking material, 19-21 parts of polyurethane, 9-12 parts of polystyrene, 4-6 parts of dihexyl glutarate, and 18-21 parts of polyimide.
2. The stretch-resistant strapping tape according to claim 1, characterized in that: The modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material is prepared by the following steps: In the first step, sulfonated polyphenylene ether, polyacrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile are dissolved in 1-methyl-2-pyrrolidone to obtain a reaction solution; In the second step, montmorillonite is added to the FeCl3 solution, ultrasonically dispersed to obtain a dispersion, and then the dispersion is added to the reaction solution, heated and stirred, and polymerized to obtain a modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material.
3. The stretch-resistant strapping tape according to claim 2, characterized in that: The mass ratio of sulfonated polyphenylene ether, polyacrylamide, ethylene glycol dimethacrylate, azobisisobutyronitrile and 1-methyl-2-pyrrolidone in the reaction solution is 5-20:5-20:1-2:1-2:200-220.
4. The stretch-resistant strapping tape according to claim 2, characterized in that: The mass ratio of montmorillonite to FeCl3 solution in the dispersion is 10-20:150-160.
5. The stretch-resistant strapping tape according to any one of claims 2 to 4, characterized in that: The mass ratio of the reaction liquid to the dispersion liquid is 220-250:160-180.
6. The stretch-resistant strapping tape according to claim 2, characterized in that: The dispersion liquid and the reaction liquid were first mixed, then heated to 55-60°C and stirred for 2 hours, and finally polymerized in an oven at 80°C for 23-24 hours.
7. A method for preparing the stretch-resistant strapping tape according to any one of claims 1 to 6, characterized in that: The following steps are involved: Modified montmorillonite / Fe 3+ Sulfonated polyphenylene ether / polyacrylamide cross-linked material, polyurethane, polystyrene, dihexyl glutarate and polyimide are put into a reaction kettle and stirred to obtain a prefabricated hot melt slurry, which is then put into an extruder, extruded into a mold, cooled and solidified, and then demolded to obtain a tensile-resistant strapping tape material.
8. The method for preparing a tensile-resistant strapping tape according to claim 7, characterized in that: The temperature in the reactor is 195-210°C, and the prefabricated hot melt slurry is prepared by stirring at a speed of 300r / min for 2h with a stirring device, and the extrusion temperature of the twin-screw extruder is 195-210°C.
Citation Information
Patent Citations
Preparation method of tensile packing belt material
CN110028775A